Characterization of an arabinogalactan isolated from gum exudate of Odina wodier Roxb.: Rheology, AFM, Raman and CD spectroscopy. (15th December 2020) - De, Arnab; Malpani, Deepika; Das, Bhaskar; Mitra, Debmalya; Samanta, Amalesh
Graphical abstract: Highlights: Purified gum odina (PGO) was isolated from the gum exudate of Odina wodier Roxb. plant. Rheological study, AFM, Raman and CD spectroscopy, and antioxidant activities of PGO were examined. Rheology of PGO dispersions was affected by concentration, temperature and salt addition. Dynamic shear rheology of PGO dispersion showed prevalently viscous characteristic. Rheological behavior and other results of PGO are rather similar to Arabic gum. Abstract: Purified gum odina (PGO) from Odina wodier Roxb. was characterized by rheology, AFM, Raman and CD spectroscopy, in vitro antioxidant activity against hydroxyl radical and superoxide radical, and total antioxidant capacity. The PGO dispersions exhibited pseudoplastic behaviour. The viscosity of dispersion increased with increasing PGO concentration, but decreased with increasing temperature and added salt concentration. The loss modulus was higher than storage modulus indicating prevalently viscous characteristics. AFM analysis showed irregular spherical lumps due to inter- and intramolecular interactions. The Raman spectrum of PGO was similar to that of gum arabic. Circular dichroism revealed partial adoption of polyproline II type conformation, suggesting a less compact structure. The PGO was found to scavenge hydroxyl radical (IC50 517.68 ± 3.60 μg/mL) and superoxide radical (IC50 586.21 ± 3.41 μg/mL), and possess total antioxidant capacity (9.64 ± 0.23 mg gallic acid equivalent/g). Overall, this work would exploit PGO as a new hydrocolloid source in the food and pharmaceutical industries.